APLIKASI PASURUAN CITY GUIDE BERBASIS ANDROID DENGAN MENGGUNAKAN METODE LBS (LOCATION BASED SERVICE) - Sigit Riyadi; Muhammad Afif (SPIRIT, 2021)
Abstract: Smart City is a term in assessing a City that has succeeded in utilizing Information Technology as a means of supporting the government and the community in providing facilities and services. Based on the SmartCity concept, an Android-based "Pasuruan City Guide" application will be made using the LBS (Location Based Service) method, in accordance with the name of the application, the city that will be used as a research isPasuruan, the "Pasuruan City Guide" application will display Service information Public, besides that there is also Pasuruan City Event information.Keywords: Pasuruan City Guide, LBS, Public, Event, Android